2004
DOI: 10.1124/jpet.104.072413
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Tumor Cell Proliferation by σ Ligands Is Associated with K+ Channel Inhibition and p27kip1 Accumulation

Abstract: Previous studies have shown that receptors are overexpressed in tumor cells. However, the role of receptors remains enigmatic. Recently, we and others have demonstrated that -1 receptor modulates K ϩ channels in pituitary. In the present report, patch-clamp and Western blot assays were used in small cell lung cancer (SCLC, NCI-H209, and NCI-H146) and leukemic (Jurkat) cell lines to investigate the effects of ligands on voltage-gated K ϩ channels and cell proliferation. The ligands (ϩ)-pentazocine, igmesine, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
50
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 33 publications
9
50
0
Order By: Relevance
“…The same modulation of cell cycle-controlling proteins was also observed for cells challenged with igmesine (Fig. 4) and other sigma ligands (25), suggesting a common pathway.…”
Section: Igmesine and Nppb Inhibit Cell Proliferation Through P27 Kip1supporting
confidence: 73%
See 4 more Smart Citations
“…The same modulation of cell cycle-controlling proteins was also observed for cells challenged with igmesine (Fig. 4) and other sigma ligands (25), suggesting a common pathway.…”
Section: Igmesine and Nppb Inhibit Cell Proliferation Through P27 Kip1supporting
confidence: 73%
“…In a previous work, we have demonstrated that the pharmacological activation of these receptors by igmesine blocked tumor cell cycle through a mechanism involving the inhibition voltage-dependent K ϩ channels (25). Altogether, our data showing the modulation of both potassium and chloride flux across the membrane by sigma ligands indicate that the sigma-1 receptors modulate the RVD process.…”
Section: Heksupporting
confidence: 72%
See 3 more Smart Citations